Implications of instrumental and ritual stances for traditionalism–threat responsivity relationships. (10th November 2022) - Samore, Theodore; Fessler, Daniel M. T.
Abstract: Jagiello et al.'s bifocal stance theory provides a useful theoretical framework for attempting to understand the connection between greater adherence to traditional norms and greater sensitivity to threats in the world. Here, we examine the implications of the instrumental and ritual stances with regard to various evolutionary explanations for traditionalism–threat sensitivity linkages.